Differential Gene Expression Patterns Between Apical and Basal Inner Hair Cells Revealed by RNA-Seq - Tang, Feng; Chen, Xiaoling; Jia, Lifeng; Li, Hai; Li, Jingya; Yuan, Wei (Frontiers in Molecular Neuroscience, 2020)
Tonotopic differences in the structure and physiological function, e.g. synapse number, membrane properties, Ca2+ channels, Ca2+ dependence of exocytosis and vesicle pool replenishment of inner hair cells (IHCs) along the longitudinal cochlear axis have recently been discovered, suggesting different gene expression patterns of IHCs. To determine whether IHCs present different gene expression patterns along the longitudinal cochlear axis, apical and basal IHCs were collected separately using the suction pipette technique from adult mouse cochleae for RNA-seq and genome-wide transcriptome analysis. We found 689 annotated genes showed more than 2-fold increase in expression. Interestingly, 93.4% of the differentially expressed genes (DEGs) was upregulated in apical IHCs. Although a subset of genes that related to IHC machinery and deafness were found to be differentially expressed, a gradient of gene expression was indeed detected in Ocm, Pvalb, Prkd1, Fbxo32, Nme2 and Sncg, which may play putative roles in the Ca2+ buffering and survival regulation. The expression of these genes was validated by real-time quantitative PCR (RT-qPCR) or immunocytochemistry. We conclude that IHCs from different mouse cochlear longitudinal position have different gene expression profiles. Our data might serve as a valuable resource for exploring the molecular mechanisms underlying different biological properties as well as the survival regulation of IHCs.